Nivolumab plus ipilimumab, with or without enzalutamide, in AR‐V7‐expressing metastatic castration‐resistant prostate cancer: A phase‐2 nonrandomized clinical trial. Issue 6 (26th February 2021) - Shenderov, Eugene; Boudadi, Karim; Fu, Wei; Wang, Hao; Sullivan, Rana; Jordan, Alice; Dowling, Donna; Harb, Rana; Schonhoft, Joseph; Jendrisak, Adam; Carducci, Michael A.; Eisenberger, Mario A.; et al.
Abstract: Background: AR‐V7‐positive metastatic prostate cancer is a lethal phenotype with few treatment options and poor survival. Methods: The two‐cohort nonrandomized Phase 2 study of combined immune checkpoint blockade for AR‐V7–expressing metastatic castration‐resistant prostate cancer (STARVE‐PC) evaluated nivolumab (3 mg/kg) plus ipilimumab (1 mg/kg), without (Cohort 1) or with (Cohort 2) the anti‐androgen enzalutamide. Co‐primary endpoints were safety and prostate‐specific antigen (PSA) response rate. Secondary endpoints included time‐to‐PSA‐progression‐free survival (PSA‐PFS), time‐to‐clinical/radiographic‐PFS, objective response rate (ORR), PFS lasting greater than 24 weeks, and overall survival (OS). Results: Thirty patients were treated with ipilimumab plus nivolumab ( N  = 15, Cohort 1, previously reported), or ipilimumab plus nivolumab and enzalutamide ( N  = 15, Cohort 2) in patients previously progressing on enzalutamide monotherapy. PSA response rate was 2/15 (13%) in cohort 1 and 0/15 in cohort 2, ORR was 2/8 (25%) in Cohort 1 and 0/9 in Cohort 2 in those with measureable disease, median PSA‐PFS was 3.0 (95% confidence interval [CI]: 2.1–NR) in cohort 1 and 2.7 (95% CI: 2.1–5.9) months in cohort 2, and median PFS was 3.7 (95% CI: 2.8–7.5) in cohort 1 and 2.9 (95% CI: 1.3–5.8) months in cohort 2. Three of 15 patients in cohort 1 (20%, 95% CI: 7.1%–45.2%) and 4/15 patients (26.7%, 95% CI: 10.5%–52.4%) in cohort 2 achieved a durable PFS lasting greater than 24 weeks. Median OS was 8.2 (95% CI: 5.5–10.4) in cohort 1 and 14.2 (95% CI: 8.5–NA) months in cohort 2. Efficacy results were not statistically different between cohorts. Grade‐3/4 adverse events occurred in 7/15 cohort 1 patients (46%) and 8/15 cohort 2 patients (53%). Combined cohort ( N  = 30) baseline alkaline phosphatase and cytokine analysis suggested improved OS for patients with lower alkaline phosphatase (hazards ratio [HR], 0.30; 95% CI: 0.11–0.82), lower circulating interleukin‐7 (IL‐7) (HR, 0.24; 95% Cl: 0.06–0.93) and IL‐6 (HR, 0.13; 95% Cl: 0.03–0.52) levels, and higher circulating IL‐17 (HR, 4.53; 95% CI: 1.47–13.93) levels. There was a trend towards improved outcomes in men with low sPD‐L1 serum levels. Conclusion: Nivolumab plus ipilimumab demonstrated only modest activity in patients with AR‐V7‐expressing prostate cancer, and was not sufficient to justify further exploration in unselected patients. Stratification by baseline alkaline phosphatase and cytokines (IL‐6, −7, and −17) may be prognostic for outcomes to immunotherapy.